Macrophage recruitment by fibrocystin‐defective biliary epithelial cells promotes portal fibrosis in congenital hepatic fibrosis. Issue 3 (16th January 2016) - Locatelli, Luigi; Cadamuro, Massimiliano; Spirlì, Carlo; Fiorotto, Romina; Lecchi, Silvia; Morell, Carola Maria; Popov, Yury; Scirpo, Roberto; De Matteis, Maria; Amenduni, Mariangela; Pietrobattista, Andrea; Torre, Giuliano; et al.
Abstract : Congenital hepatic fibrosis (CHF) is a disease of the biliary epithelium characterized by bile duct changes resembling ductal plate malformations and by progressive peribiliary fibrosis, in the absence of overt necroinflammation. Progressive liver fibrosis leads to portal hypertension and liver failure; however, the mechanisms leading to fibrosis in CHF remain elusive. CHF is caused by mutations in PKHD1, a gene encoding for fibrocystin, a ciliary protein expressed in cholangiocytes. Using a fibrocystin‐defective ( Pkhd1 del4/del4 ) mouse, which is orthologous of CHF, we show that Pkhd1 del4/del4 cholangiocytes are characterized by a β‐catenin‐dependent secretion of a range of chemokines, including chemokine (C‐X‐C motif) ligands 1, 10, and 12, which stimulate bone marrow‐derived macrophage recruitment. We also show that Pkhd1 del4/del4 cholangiocytes, in turn, respond to proinflammatory cytokines released by macrophages by up‐regulating αvβ6 integrin, an activator of latent local transforming growth factor‐β1. While the macrophage infiltrate is initially dominated by the M1 phenotype, the profibrogenic M2 phenotype increases with disease progression, along with the number of portal myofibroblasts. Consistent with these findings, clodronate‐induced macrophage depletion results in a significant reduction of portal fibrosis and portal hypertension as well as of liver cysts. Conclusion: Fibrosis can be initiated by an epithelial cell dysfunction, leading to low‐grade inflammation, macrophage recruitment, and collagen deposition; these findings establish a new paradigm for biliary fibrosis and represent a model to understand the relationship between cell dysfunction, parainflammation, liver fibrosis, and macrophage polarization over time. (Hepatology 2016;63:965–982)